Maniava Skete as a Citadel of the Christian Faith and Selflessness - Lytvyn, Mykola; Tsependa, Ihor (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
Review of the monograph “The Great Skete in the Carpathians. In three volumes.” / Ed. by M. V. Kuhutiak. Volume 1. Ivano-Frankivsk: Manuskrypt-Lviv, 2013. 728 p. Volume 2. Ivano-Frankivsk: Manuskrypt-Lviv, 2015. 514 p. Volume 3. Ivano-Frankivsk, 2017. 576 p.